An alternative route for petroclival tumors: Without mastoidectomy and superior petrosal sinus ligation: A cadaveric study - Özbek, Muhammet Arif; Başak, Ahmet Tulgar (Wolters Kluwer Medknow Publications, 2023)
Objective: Retrosigmoid approach and presigmoid approach and its derivatives including retrolabyrinthine, translabyrinthine, and transpetrosal approaches have long been used for reaching posterior and middle cranial fossa. In neurosurgery perspective, many types of tumors arise extradurally and surgical resection of these tumors is still challenging. We aimed to describe a modified way to approach posterior and middle fossa to contribute to the surgical management of petroclival tumors with posterior extension. Methods: Modified sigmoid approaches were performed bilaterally in 5 fresh adult cadaver heads. Results: In this approach, it was possible to reach the middle and posterior fossa with a single craniotomy. Temporal dura matter was dissected from the temporal bone with extradural gentle dissection. In addition, sigmoid sinus and superior petrosal sinus (SPS) were dissected off from the petrous bone meticulously. Subsequently, the posterolateral superior arcuate petrosectomy was performed with high-speed surgical drill extradurally by protecting the semicircular canal, labyrinthine channel, and cochlea. Dura matter was elevated for 1.5 cm with retractor above the mastoid bone. Dura was opened from an alternative area of Trautmann’s triangle. After having exposed and opened the dura, posterior fossa was reached at the level of 7.-8. cranial nerves. Conclusion: We described an alternative route which seems to be a feasible way to reach posterior and middle fossa without mastoidectomy and SPS ligation. Notably, this technique can be applicable to petroclival tumor surgery after more anatomic studies with cadaveric specimens.
Keywords: Extradural Sigmoid Approach; Petroclival Tumors; Without Mastoidectomy; Without Superior Petrosal Sinus Ligation